EMBRACING SUSTAINABLE DEVELOPMENT GOALS CRITICALLY TO EXPLORE LIFE PURPOSES IN ENGLISH LANGUAGE TEACHER EDUCATION - Mambu, Joseph Ernest (TEFLIN Journal, 2023)
English language teacher education is not only about making students who learn to teach English focus on language teaching, learning, and use but also about how teacher educators can delve into the life purposes of themselves, their students, and their students’ learners. The role of a language teacher educator is hence pivotal in orchestrating learning materials and activities that allow students to explore life purposes at individual, community, and international levels. As a scholar interested in critical language teacher education, one of my life purposes is to nurture my students’ criticality. To illustrate how my student performed criticality over time, in a case study, I explored my dialogue on Sustainable Development Goals (SDGs) as a learning material with one focal student in my Critical Pedagogy & Literacy class from January to April 2019 and beyond, even after she graduated. Criticality was demonstrated when she problematized oppressive words and actions and envisioned social transformation as she learned (to teach) English. A narrative analysis of the data also suggests that the student’s life purpose (e.g., to empower her fellow Papuan people) aligns with that of her instructor and her Papuan English language learners. Implications for critical language teacher education are discussed.